2021
DOI: 10.3390/catal11091026
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation on NixMg1−xAl2O4: A Comparative Study of MgAl2O4 and NiAl2O4

Abstract: Due to the increasing attention focused on global warming, many studies on reducing CO2 emissions and developing sustainable energy strategies have recently been performed. One of the approaches is CO2 methanation, transforming CO2 into methane. Such transformation (CO2 + 4H2 → CH4 + 2H2O) provides advantages of carbon liquification, storage, etc. In this study, we investigated CO2 methanation on nickel–magnesium–alumina catalysts both experimentally and computationally. We synthesized the catalysts using a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Thus, these samples retained active sites despite the sintering of platinum during aging. Transition metal aluminate spinels were previously observed to be effective CO adsorbents, in which the strength of interaction is heavily influenced by the divalent cation [25][26][27][28]. The previous literature further observed that CO adsorption on aluminate spinels was significantly enhanced through the incorporation of multiple transition metal elements, as well as under-coordinated defect sites [29][30][31].…”
Section: Methodsmentioning
confidence: 97%
“…Thus, these samples retained active sites despite the sintering of platinum during aging. Transition metal aluminate spinels were previously observed to be effective CO adsorbents, in which the strength of interaction is heavily influenced by the divalent cation [25][26][27][28]. The previous literature further observed that CO adsorption on aluminate spinels was significantly enhanced through the incorporation of multiple transition metal elements, as well as under-coordinated defect sites [29][30][31].…”
Section: Methodsmentioning
confidence: 97%
“…Owing to excellent thermal, chemical & mechanical stability & unique electro-optic characteristics, it has been under study for metal containing ceramic-composites, and radiation protection applications [ [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. It has also been extensively deliberated for catalytic applications owing to its unique porous structure [ [21] , [22] , [23] , [24] ]. The most important claim for NiAl 2 O 4 is its potential application as metamaterial owing to its distinctive dielectric response [ 25 ].…”
Section: Introductionmentioning
confidence: 99%